Online Game and Children's Communication Ability - Desiana; Marlina (Budapest International Research and Critics University, 2022)
After the implementation of distance learning with internet-based media such as Zoom and Google Meet, children are getting closer to their activities with gadgets. Many children are increasingly sticky and difficult to separate from their gadgets, even children often become addicted to gadgets. This study involving 15 children aims to see the effect of playing online games by children on children's ability to communicate, this research was conducted at SMP N 6 Panyabungan. The results of this study found that first, children who have control over the use of gadgets from their parents will have good communication patterns and skyrocket their achievements, second, children who are not controlled by their parents in the use of gadgets then they have a tendency to be aloof and difficult to communicate. Third, children show other symptoms of gadget addiction by playing online games, namely lack of concentration and seem unfocused when spoken to, fourth, children tend to have unstable emotions when angry or use words they often hear when playing online games.